A mixed control chart using process capability index. Issue 2 (3rd April 2017) - Aslam, Muhammad; Khan, N.; Ahmad, Liaquat; Jun, Chi-Hyuck; Hussain, Jaffer
ABSTRACT: Control charts are considered as a compulsory tool for the monitoring and improvement of the quality of products. The commonly used attribute and the variable control charts are unsatisfactory for process monitoring. To overcome this diﬃculty, we proposed a monitoring scheme that is an improved technique based on the joint merits of the attribute as well as the variable control charts. The control chart coeﬃcients have been determined for in-control and out-of-control situations for specified average run length values using simulation. The eﬃciency of the proposed control chart has been evaluated using average run length criteria for different values of the process settings. A practical example has been studied for implementation of the proposed technique. It has been observed that the proposed chart performs well for the mixed technique under the process capability index.